Foreign Affiliates in OECD Economies Presence, Performance and Contribution to Host Countries' Growth - Criscuolo, Chiara (OECD Publishing, 2006)
In recent decades, foreign direct investment (FDI) has steadily increased so that foreign owned multinational enterprises (MNEs) now play an important role in the economy of many developed and developing economies. Countries compete with each other to attract FDI because they expect affiliates of foreign MNEs to contribute to the welfare of the host economy through multiple channels. But what precisely is the impact of foreign affiliates on the host country economy?
Keywords: Economics